Method Improvement and Effect Analysis of Triaxial Compression Acoustic Emission Test for Coal and Rock - Yan Zhou; Chuanxiao Liu; Depeng Ma (Advances in Civil Engineering)
In the study of the acoustic emission (AE) characteristics of rock samples or coal samples under triaxial compression conditions, most scholars carry out relevant experiments by placing the AE detector on the outer wall of the triaxial chamber of the rock mechanics test system. Owing to the continuous obstruction of AE signals by hydraulic oil in the triaxial chamber and the frequent interference of external noises, the final experimental data cannot objectively and truly reflect the essential characteristics of AE of rock or coal under triaxial compression conditions. It is difficult to scientifically guide and accurately predict precursory information of rock’s or coal’s rupture and instability. Based on this, a series of improvements and optimizations were made to the original triaxial compression AE test method, which is based on the modification of the communication interface of the rock mechanics test system, a test head which can put the AE detector into the triaxial chamber and withstands high confining pressure, in order to obtain the true, comprehensive, and reliable AE signals. It is of considerable significance to the scientific determination of the precursory characteristics of rock’s or coal’s rupture and instability.